2024
DOI: 10.3390/healthcare12010114
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Response to the Physical and Psycho-Social Care Needs of Patients with COVID-19: A Mixed-Methods Study

Angela Tolotti,
Loris Bonetti,
Corina Elena Luca
et al.

Abstract: The COVID-19 pandemic heavily impacted nursing care. This study aimed to understand which nursing interventions were instrumental in responding to COVID-19 patients’ needs by exploring the experiences of patients and nurses. In this mixed-method study with an explanatory sequential design, we involved nurses caring for COVID-19 patients in intensive and sub-intensive care units and patients. In the first phase, we collected data through a survey that assessed patients’ needs from the perspective of nurses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…As for the focus on the COVID-19 vaccines, although the pandemic is officially over, it is essential not to forget the lessons that can be learned from it for similar future cases [21]. Studies have shown that anti-vaccine posts on social media may facilitate anti-vaccination behavior [19] and that tendencies of vaccine hesitancy and rejection are related to belief in conspiracy theories [8,22,23]. These aspects, along with the prevalent use of vaccine opponents in social media platforms to share their worldviews [12], indicate the importance of studying the characteristics of the discourse in these platforms.…”
Section: Introductionmentioning
confidence: 99%
“…As for the focus on the COVID-19 vaccines, although the pandemic is officially over, it is essential not to forget the lessons that can be learned from it for similar future cases [21]. Studies have shown that anti-vaccine posts on social media may facilitate anti-vaccination behavior [19] and that tendencies of vaccine hesitancy and rejection are related to belief in conspiracy theories [8,22,23]. These aspects, along with the prevalent use of vaccine opponents in social media platforms to share their worldviews [12], indicate the importance of studying the characteristics of the discourse in these platforms.…”
Section: Introductionmentioning
confidence: 99%